How Promotion Incentives and Online Comments Drive Purchases of Originote Moisturizer on Shopee Live Through Perceived Trust - Belinda Lia Savera; Dina Lusianti; Dian Wismar’ein (Al-Muhasabah: Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
With the advancement of time, many new phenomena have emerged, including the use of live streaming in the buying and selling of products. This trend is evident in e-commerce platforms, one of which is Shopee. Shopee has a feature called Shopee Live that is frequently used to help sellers promote their products. This study aims to analyze the influence of promotion incentives and online comments on impulsive buying, with perceived trust as an intervening variable (focused on Shopee live streaming consumers). The research employs a quantitative method with purposive sampling, to collect 135 samples. The analysis is conducted using Structural Equation Model with calculations performed through the AMOS 24.0 program. The results indicate that promotion incentive information has a positive and significant effect on impulsive buying behavior, online comments have a positive and significant effect on impulsive buying behavior, promotion incentive information has a positive and significant effect on perceived trust, online comments have a positive and significant effect on perceived trust, and perceived trust has a positive and significant effect on impulsive buying behavior. However, perceived trust cannot mediate the relationship between promotion incentive information and online comments on impulsive buying behavior.